Differental diagnosis of painless lymphadenopathy: challenges in everyday clinical practice with case report and literature overview - Marković, Marija; Miljković, Ana (General Practice, 2025)
Introduction. Lymphadenopathy is defined as an abnormalfinding during a physical examination, indicatingthat the lymph nodes are abnormal in size, consistency, andnumber. A thorough personal history and detailed physicalexamination allow the physician to formulate an appropriatediagnostic strategy. It is important to approach differentialdiagnoses with caution, as there is a wide range of potentialcauses and often nonspecific clinical presentations. Painlesslymphadenopathy, in particular, presents a significant clinicalchallenge, especially in primary healthcare settings.Case report 1. A 54-year-old female patient presentedwith a lump that she had noticed in her left groin. A detailedphysical examination revealed a painless lump measuring25 mm in diameter. An ultrasound of the groin showed anenlarged lymph node with peripheral vascularization. A biopsyof the lymph node confirmed the presence of metastaticcervical carcinoma. A PET-CT scan indicated a solitary lumpalong the upper uterine margin, along with liver metastases.The oncology team recommended three weeks of chemotherapy.The patient has since undergone six cycles of chemotherapy.Case report 2. A 76-year-old male patient presentedwith a lump in his right armpit that had been present for severalmonths, but he reported no other symptoms. A physicalexamination revealed a lump the size of an apple located underthe right armpit, which was painless to the touch. A biopsyconfirmed that it was a metastatic melanoma. An abdominalultrasound showed the presence of liver metastases. A dermatologicalexamination revealed a suspicious skin tumor in thelumbar area, measuring 1 cm in diameter, also highly suggestiveof melanoma. After excising the lesion, the pathologicalfindings confirmed the diagnosis.Conclusion. Painless lymphadenopathy is a commonfinding that presents diagnostic challenges, with a broadrange of causes that can vary from benign to malignant.Timely recognition and appropriate interventions are crucialfor treatment outcomes.
Keywords: melanoma malignum; lymphatic metastases; Uterine Cervical Neoplasms